Nanoscopic localization of surface-exposed antigens of Borrelia burgdorferi - Lemgruber, Leandro; Sant’Anna, Celso; Griffths, Caron; Abud, Yuri; Mhlanga, Musa; Wallich, Reinhard; Frischknecht, Friedrich (Microscopy and microanalysis, 2015)
Borrelia burgdorferi sensu lato, the causative agent of Lyme disease, is transmitted to humans through the bite of infected Ixodes spp. ticks. Successful infection of vertebrate hosts necessitates sophisticated means of the pathogen to escape the vertebrates’ immune system. One strategy employed by Lyme disease spirochetes to evade adaptive immunity involves a highly coordinated regulation of the expression of outer surface proteins that is vital for infection, dissemination, and persistence. Here we characterized the expression pattern of bacterial surface antigens using different microscopy techniques, from fluorescent wide field to super-resolution and immunogold-scanning electron microscopy. A fluorescent strain of B. burgdorferi spirochetes was labeled with monoclonal antibodies directed against various bacterial surface antigens. Our results indicate that OspA is more evenly distributed over the surface than OspB and OspC that were present as punctate areas.
Gesehen am 17.06.2020